Analysis on steel-concrete joint section of hybrid girder cable-stayed bridge. Issue 2 (April 2019) - Guo, Junfeng
Abstract: Hybrid girder cable-stayed bridge has some advantages, such as structure mechanism performance and the low cost. In China, more and more cable-stayed bridge with hybrid girder appeared. The steel–concrete joint part is one of the key structures of large span cable-stayed bridge with hybrid girder, the static bearing capacity and fatigue performance of steel–concrete joint part structure is directly related to security and durability of the bridge. Through the finite element simulation calculation, the stress distribution is calculated, and the stress distribution of the steel structure top plate, steel structure baseplate, concrete top plate and concrete baseplate is analysed emphatically. Verify the bearing capacity and safety of the structural design of joint section.